PENCEGAHAN KORUPSI (KAJIAN PEMIKIRAN MAO TSE-TUNG) - Michael, Tomy (Jurnal Selat, 2016)
Characteristic of the leader can apply with Thought of Mao Tse-Tung which âPut on the ideas of the citizenry and focus in that ideas, then you give it back to the citizenry in order that ideas, and if that happen with the ideas you must correct it. It is the basic method of leadership. âThe conclusion of Thought of Mao Tse-Tungâ is appropriate to apply in fighting against of corruption because of The Letter of the Act of Republic of Indonesia Number 20 of 2001 concerning changes ofThe Letter of the Act Number 31 of 1999 concerning Eradicationâs Act of Punishment in Corruption was created the justice for the society when the corruptors are accused the corruption. The point of view is takes the profit with the president as a executive leader then the president can become a subject of law with distinct character. Keywords: Corruption, Mao Tse-Tung, leader.   Ciri khas pemimpin bisa diterapkan sesuai pemikiran Mao Tse-Tung yaitu âBersandar pada gagasan masyarakat dan fokus pada gagasan itu, lalu berikanlah kembali gagasan tersebut kepada masyarakat dan itulah gagasan sebenarnya. Ini adalah metode dasar kepemimpinan.â Kesimpulannya bahwa pemikiran Mao Tse-Tung adalah tepat untuk diterapkan dalam memerangi korupsi karena Undang-Undang Republik Indonesia Nomor 20 Tahun 2001 tentang Perubahan Atas Undang-Undang Nomor 31 Tahun 1999 Tentang Pemberantasan Tindak Pidana Korupsi telah menciptakan keadilan bagi masyarakat saat koruptor dituduh melakukan korupsi. Hal lainnya presiden sebagai kepala eksekutif maka presiden dapat menjadi subjek hukum yang bersifat tegas. Adanya sikap yang tegas ini akan menimbulkan dampak kepada penegak hukum untuk menerapkan peraturan perundang-undangan secara adil. Kata kunci: Korupsi, Pemberantasan, Mao Tse-Tung